2019
DOI: 10.1002/jcb.28756
|View full text |Cite|
|
Sign up to set email alerts
|

Methyl helicterate inhibits hepatic stellate cell activation through downregulating the ERK1/2 signaling pathway

Abstract: The present study was to investigate the inhibitory effect of methyl helicterate (MH) on hepatic stellate cells (HSC‐T6), primarily elucidating the underlying mechanism of MH against liver fibrosis. HSC‐T6 cells were activated by platelet‐derived growth factor (PDGF) stimulation, and then the effects of MH on cell viability, cytomembrane integrity, colony, migration, apoptosis, and cell cycle were detected. Moreover, the regulative mechanism of MH on HSCs was investigated by detecting the activation of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…After 24 hours, cells were treated with drugs as described above for 168 hours. The cells were added methanol then fixed with 0.1% crystal violet for visualization of colonies 15 …”
Section: Methodsmentioning
confidence: 99%
“…After 24 hours, cells were treated with drugs as described above for 168 hours. The cells were added methanol then fixed with 0.1% crystal violet for visualization of colonies 15 …”
Section: Methodsmentioning
confidence: 99%
“…The influence of Fos on stellate cells has been reported in several studies. Wei et al showed that methyl helicterate treatment in hepatic stellate cells (HSCs) inhibited the expression of Fos, a downstream nuclear transcription factor of extracellular regulated protein kinases1/2 (ERK1/2) signaling pathway, and participated in many physiological processes (30). Gao et al showed that the transient induction of Fos gene activation and expression was involved in connective tissue growth factor (CCN2)-stimulated HSCs DNA synthesis and cell proliferation via activating ERK1/2 signaling pathway (31).…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al. showed that methyl helicterate treatment in hepatic stellate cells (HSCs) inhibited the expression of Fos , a downstream nuclear transcription factor of extracellular regulated protein kinases1/2 (ERK1/2) signaling pathway, and participated in many physiological processes ( 30 ). Gao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that ERK1/2 signaling is the main regulator that promotes the progression of human hepatocellular carcinoma ( 30 34 ). ERK1/2 participates in liver injury in human liver stem cells ( 35 , 36 ). Also, the aggressive behavior of HCC cells has a positive relationship with the level of phosphorylated ERK and activated level of hepatic stellate cells (aHSCs) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%